2000
DOI: 10.1016/s0006-3495(00)76439-3
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Dynamics Simulations of Sialyl-Lewisx/E-selectin-Mediated Rolling in a Cell-Free System

Abstract: Selectin-mediated leukocyte rolling is crucial for the proper function of the immune response. Recently, selectin-mediated rolling was recreated in a cell-free system (Biophysical Journal 71:2902-2907 (1996)); it was shown that sialyl Lewis(x) (sLe(x))-coated microspheres roll over E-selectin-coated surfaces under hydrodynamic flow. The cell-free system removes many confounding cellular features, such as cell deformability and signaling, allowing us to focus on the role of carbohydrate/selectin physical chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 48 publications
7
64
0
Order By: Relevance
“…For HCC cells, the viscoelasticity has probably significant bearing on tumor cell invasion and metastasis, in which it determines the flowing behavior of tumor cells in the circulation and whether such cells can be arrested to form metastasis. In addition, mechanical stiffness is closely related to cell adhesion behavior [26,27] , which is the first step in tumor cell invasion. With the three-element standard linear solid viscoelastic model, we clearly showed that HCC cells have higher values for the elastic coefficients but not the viscous coefficient than hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For HCC cells, the viscoelasticity has probably significant bearing on tumor cell invasion and metastasis, in which it determines the flowing behavior of tumor cells in the circulation and whether such cells can be arrested to form metastasis. In addition, mechanical stiffness is closely related to cell adhesion behavior [26,27] , which is the first step in tumor cell invasion. With the three-element standard linear solid viscoelastic model, we clearly showed that HCC cells have higher values for the elastic coefficients but not the viscous coefficient than hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical basis for the exceptional ability of selectins to mediate cell capture (tethering) and rolling adhesions under highly disruptive forces is still obscure (3)(4)(5)(6). This ability has been primarily attributed to fast formation rates of selectin bonds and to the ability of selectin tethers to tolerate rupture by elevated shear forces (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…This calculation was done for a hard sphere rolling over a ligand-coated substrate in Couette flow. The approximation of a hard sphere was appropriate because we had developed "cell-free" rolling in which the dynamics of rolling was recreated by decorating hard spheres with a selectin ligand, such as the tetra-saccharide sialyl-Lewis x [17]; we have made rigorous comparisons between the dynamics of bead rolling and the results of simulations [18] to verify that the model was correct. The left panel shows a spatio-temporal map of bonds in the contact zone between a bead and surface, in the reference frame of the bead, with each line segment indicating a bond, and red bonds under strain.…”
Section: Relating Bond Mechanics To Dynamics Of Adhesionmentioning
confidence: 99%